2015
DOI: 10.1159/000430312
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Haemeoxygenase-1 Directly Improves Endothelial Function in Isolated Aortas from Obese Rats through the Ampk-Pi3k/Akt-Enos Pathway

Abstract: Background: Induction of haemeoxygenase-1 (HO-1) increases adiponectin secretion by remodeling adipose tissue in obesity. The objective of our study is to explore whether HO-1 induction directly improves endothelial function independent of adiponectin changes in obese rats. Methods: Rats were divided into control and obesity groups. Aortic endothelial function was determined by measuring endothelium-dependent vasodilatation (EDV). Vascular segments of the obese rats were incubated in an organ bath in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…NF-κB is a host of proinflammatory master switch and also inducible transcription factors which are capable of controlling the production of some inflammatory factors [36]. In the vascular endothelium, NF-κB activation induces the expression of proinflammatory genes, including those encoding adhesion molecules, cytokines, and chemoattractant proteins, which collectively contribute to the initiation and development of atherosclerosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a host of proinflammatory master switch and also inducible transcription factors which are capable of controlling the production of some inflammatory factors [36]. In the vascular endothelium, NF-κB activation induces the expression of proinflammatory genes, including those encoding adhesion molecules, cytokines, and chemoattractant proteins, which collectively contribute to the initiation and development of atherosclerosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that irisin may upregulate the HO-1/adiponectin axis and further activate AMPK-eNOS pathway to improve PVAT function through an endothelium-dependent pathway [12, 17]. Upregulation of HO-1/adiponectin axis could also activate the AMPK-eNOS signaling pathway [16]. In addition, we also found that blocking the AMPK-eNOS pathway could abolish beneficial effects of irisin-treated PVAT on endothelial function.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, many studies have demonstrated that induction of HO-1/adiponectin axis have beneficial effects on cardiovascular disease [16]. Both HO-1 and adiponectin have powerful anti-oxidative and anti-inflammatory properties that protect endothelial dysfunction by enhancing NO production [29-32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMP-activated protein kinase (AMPK) activation counteracts endothelial injury in endothelial cells [31-33]. C1q/TNF-related protein 9 is shown to alleviate TNFα-induced expressions of VCAM-1 and MCP-1 via AMPK activation in endothelial cells [34].…”
Section: Resultsmentioning
confidence: 99%